Processing method for self-generating metal-graphene composite thermal interface material

By forming nanometal particles between graphene grids, the existing graphene-based heat dissipation materials have been solved, and the problems of poor fatigue resistance, reduced thermal conductivity and high cost are achieved, and efficient, economical and environmentally friendly thermal interface materials are achieved.

CN119890055AActive Publication Date: 2025-04-25GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510071848.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing graphene-based heat dissipation materials have problems such as poor fatigue resistance, reduced thermal conductivity, and high costs, which cannot meet the efficient heat dissipation needs of modern electronic equipment.

Method used

Using the processing method of self-generating metal-graphene composite thermal interface material, nanometal particles are formed to fill the graphene grids by mixing graphene, metal salt and reducing agent, thereby enhancing the thermal conductivity and mechanical strength of the material.

Benefits of technology

It realizes the high thermal conductivity, mechanical strength and economy of thermal interface materials, is convenient to produce and use, and is more environmentally friendly, meeting the efficient heat dissipation needs of modern electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890055A_ABST
    Figure CN119890055A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal interface materials, and discloses a processing method of a self-generated metal-graphene composite thermal interface material, which is applied to chip processing, and comprises the following steps: adding graphene and derivatives thereof, metal salt, ceramic and other high thermal conductivity particles and a reducing agent into water or an alcohol solvent, and carrying out dispersion treatment to obtain a mixed solution A; adding at least one of silicone grease or silicone resin, and dispersing to obtain slurry B; and coating the solvent on the heat dissipation surface of the to-be-processed chip, covering the heat dissipation sheet, heating to trigger a reaction, keeping the reaction to be dry, volatilizing the solvent in the drying process, generating metal between the heat dissipation surface and the heat dissipation sheet until the solvent is completely volatilized, and fixing the heat dissipation sheet on the heat dissipation surface of the chip. Metal salt is reduced into nano metal particles through a reducing agent, so that graphene grids are filled with the nano metal particles, and the nano metal composite graphene thermal interface material is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal interface materials, and in particular to a processing method of a self-generated metal-graphene composite thermal interface material. Background Art

[0002] As electronic devices develop towards high performance and miniaturization, the power density of chips continues to increase, and the heat generated increases significantly. In order to ensure the stable operation of chips and electronic devices under high temperature conditions, heat dissipation technology has become a key link in improving the stability of electronic devices and extending their service life. Thermal interface materials (TIMs), as an important part of heat dissipation technology, are widely used to fill the gap between heat sources and heat sinks to improve heat transfer efficiency. However, existing thermal conductive materials are difficult to simultaneously meet the requirements of high thermal conductivity, mechanical strength and fatigue resistance, and the development of new thermal interface materials is urgently needed.

[0003] Currently, graphene is often used in heat dissipation materials for electronic devices due to its excellent thermal conductivity. Graphene film is one of the common thermal interface materials, with excellent thermal conductivity and high thermal stability. However, the cost of graphene film is relatively high, and it is easy to produce defects such as points, lines, and surfaces during the preparation process, resulting in reduced mechanical strength and thermal conductivity during long-term use. In addition, the production process of graphene is relatively complex and has a certain impact on the environment. Therefore, there is a significant demand in the market for green and environmentally friendly thermal interface materials that have high thermal conductivity, mechanical strength and economy.

[0004] Current graphene-based heat dissipation materials have problems such as poor fatigue resistance, reduced thermal conductivity, and high cost, and cannot meet the efficient heat dissipation needs of modern electronic devices. Summary of the invention

[0005] In view of the above-mentioned defects, the purpose of the present invention is to propose a processing method for self-generated metal-graphene composite thermal interface material, enhance the connection force between graphene oxide, make the thermal interface material have thermal conductivity, mechanical strength and economy, be easy to produce and use, and be more environmentally friendly.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] A processing method for a self-generated metal-graphene composite thermal interface material is applied to chip processing, and the processing method comprises the following steps:

[0008] S1. adding graphene, metal salt and reducing agent into water or alcohol solvent, and obtaining mixed solution A through dispersion treatment;

[0009] S2. Add at least one of silicone grease or silicone resin to the mixed solution A, and disperse it to obtain slurry B;

[0010] S3. Apply slurry B to the heat dissipation surface of the chip to be processed, cover the heat dissipation surface coated with slurry B with a heat sink, and form a liquid film of slurry B between the heat dissipation surface and the heat sink;

[0011] S4. The heating triggers the reaction and is maintained until drying. During the drying process, the solvent in the liquid film evaporates, and the slurry B heats up and starts to react, causing metal to form between the heat dissipation surface and the heat sink. The distance between the heat dissipation surface and the heat sink gradually decreases until the solvent completely evaporates and the heat sink is fixed to the heat dissipation surface of the chip.

[0012] Preferably, the metal salt includes at least one element selected from the group consisting of Cu, Ag, Ni, Ti, Au, Al, Sn, Fe, and Co, and the metal salt is an organic metal salt or a hydroxide, chloride, sulfate, or nitrate of a metal.

[0013] Preferably, the organic metal salt is at least one of acetic acid, acetic acid, formic acid or acetylacetone metal salts.

[0014] Preferably, the reducing agent is at least one of ascorbic acid, glucose or hydrazine hydrate.

[0015] Preferably, the heating temperature in step S4 is 20-300°C.

[0016] Preferably, the alcohol solvent is at least one of ethanol, ethylene glycol, diethylene glycol, diethylene glycol, dipropylene glycol, glycerol or terpineol;

[0017] The graphene oxide includes graphene oxide and its derivatives, and the mass fraction of the graphene oxide in the composite material is 0.02-10%;

[0018] The mass fraction of the silicone grease or the silicone resin in the composite material is 1-10%.

[0019] The dispersant is polyethylene glycol or polyvinyl alcohol, and the mass fraction of the dispersant in the composite material is 1 to 10%;

[0020] The soldering flux contains rosin, and the mass fraction of the soldering flux in the composite material is 1-10%.

[0021] Preferably, at least one of a thickener, a sintering aid, a film-forming agent or a thixotropic agent is added;

[0022] The thickener is polyethylene glycol or polyvinyl alcohol, the sintering aid is an alkaline earth metal oxide, the film-forming agent is at least one of hydrogenated rosin, polymerized rosin or water-white rosin, and the thixotropic agent is at least one of hydrogenated castor oil or polyamide.

[0023] Preferably, high thermal conductivity particles are added, and the mass fraction of the metal salt and the high thermal conductivity particles in the composite material is 50-97%.

[0024] Preferably, when a magnetic metal is used, a magnetic field is applied in step S4, and the direction of the applied magnetic field is perpendicular to the heat dissipation surface.

[0025] Preferably, the dispersion treatment in step S1 is mechanical stirring, ultrasonic dispersion or homogeneous dispersion, and the dispersion treatment in step S2 is ultrasonic dispersion or homogeneous dispersion.

[0026] The technical solution provided by the present invention may include the following beneficial effects:

[0027] The metal salt is reduced to nano-metal particles by a reducing agent, so that these nano-metal particles are filled in the graphene grid to form a nano-metal composite graphene thermal interface material. The prepared thermal interface material has good thermal conductivity and mechanical strength, and is more economical and environmentally friendly. The production method of the thermal interface material prepared by this process is simple, easy to operate, and has high production efficiency.

[0028] The thermal interface material prepared by this scheme does not require post-processing. When in use, the slurry is directly applied to the back of the chip, heated and dried, and can be used. It is simple and efficient, and no toxic substances are produced. It is green, economical and environmentally friendly. The metal salt is reduced to nano-metal particles by a reducing agent, so that these nano-metal particles are filled in the graphene grid to form a nano-metal composite graphene thermal interface material. This process does not require the addition of catalysts or other materials, simplifies the steps, and is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A preparation circuit diagram for an embodiment of the present invention.

[0030] Figure 2 A preparation circuit diagram for another embodiment of the present invention.

[0031] Figure 3 A preparation circuit diagram for another embodiment of the present invention. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0033] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] A processing method for a self-generated metal-graphene composite thermal interface material is applied to chip processing, and the processing method comprises the following steps:

[0036] S1. adding graphene, metal salt and reducing agent into water or alcohol solvent, and obtaining mixed solution A through dispersion treatment;

[0037] S2. Add at least one of silicone grease or silicone resin to the mixed solution A, and disperse it to obtain slurry B;

[0038] S3. Apply slurry B to the heat dissipation surface of the chip to be processed, cover the heat dissipation surface coated with slurry B with a heat sink, and form a liquid film of slurry B between the heat dissipation surface and the heat sink;

[0039] S4. The heating triggers the reaction and is maintained until drying. During the drying process, the solvent in the liquid film evaporates, and the slurry B heats up and starts to react, causing metal to form between the heat dissipation surface and the heat sink. The distance between the heat dissipation surface and the heat sink gradually decreases until the solvent completely evaporates and the heat sink is fixed to the heat dissipation surface of the chip.

[0040] Most of the existing chip heat dissipation materials are graphene films, which are expensive and cause serious environmental pollution. Graphene is prone to point, line and surface defects, resulting in a decrease in the mechanical strength and thermal conductivity of the material. The self-generated metal-graphene composite thermal interface material prepared by this scheme reduces the metal salt into nano-metal particles through a reducing agent, so that these nano-metal particles are filled between the graphene oxide grids to form a nano-metal composite graphene thermal interface material. The prepared thermal interface material has good thermal conductivity and mechanical strength, and is more economical and environmentally friendly. The production method for preparing the thermal interface material layer is simple, easy to operate and has high production efficiency. When the traditional method is used to prepare the graphene metal composite thermal interface material, the centrifugal operation in the post-processing will cause the graphene to agglomerate and accelerate the agglomeration effect of the graphene. The thermal interface material prepared by this scheme does not need to be post-processed. The slurry is directly applied to the back of the chip and can be used after heating and drying. It is simple and efficient, and no toxic substances are produced. It is green, economical and environmentally friendly. At the same time, the metal salt is reduced by a reducing agent, so that metal particles are self-generated on the graphene oxide. The metal particles connect the graphene oxide to form a heat dissipation network. This process does not require the addition of catalysts or other materials, simplifies the steps, and is easy to use.

[0041] like Figure 1 In one embodiment, in step S1, graphene oxide is added to an alcohol solvent to obtain solution C, a metal salt is added to an alcohol solvent to obtain solution D, and a reducing agent is added to an alcohol solvent to obtain solution E. Solution C and solution D are first mixed and ultrasonically stirred, and finally solution E is added and ultrasonic stirring is continued.

[0042] like Figure 2 In a specific embodiment, the slurry forms a liquid film between the heat dissipation surface and the heat sink, and maintains a thickness of 0.1 to 1 mm without flowing out under the action of surface tension. Then, by heating, the metal is generated between the heat dissipation surface and the heat sink. As the solvent in the slurry evaporates, the distance between the heat dissipation surface and the heat sink gradually decreases until the solvent completely evaporates, and the heat dissipation surface and the heat sink are pressed tightly to form a thermal interface material layer.

[0043] Preferably, the metal salt includes at least one element selected from the group consisting of Cu, Ag, Ni, Ti, Au, Al, Sn, Fe, and Co, and the metal salt is an organic metal salt or a hydroxide, chloride, sulfate, or nitrate of a metal.

[0044] The above metal elements are selected, which have excellent thermal conductivity after reduction and combination with graphene. Organic metal salts or metal hydroxides are selected to avoid the use of inorganic metal salts to introduce impurities that are difficult to remove after the reaction, and solve the problem of the performance of the thermal interface material prepared by the metal paste being reduced due to impurities left over from the reaction; metal oxides are avoided to solve the problem of complex operation due to the harsh reaction conditions for the reduction of metal oxides.

[0045] Preferably, the mass fraction of the metal salt in the composite material is 10-60%.

[0046] Preferably, the organic metal salt is at least one of acetic acid, acetic acid, formic acid or acetylacetone metal salts.

[0047] When the above-mentioned organic metal salt is used to prepare thermal interface materials, the decomposition and volatilization temperature of the reduced product is low and it is easy to be decomposed and removed during the heating and drying process, thereby solving the problem of too long drying time or too high drying temperature affecting the use of metal paste when preparing thermal interface materials with metal paste.

[0048] Preferably, the reducing agent is at least one of ascorbic acid, glucose or hydrazine hydrate.

[0049] In a specific embodiment, the amount of the reducing agent used can reduce all of the metal salt or the metal hydroxide to metal element. The reducing agent is made of green and environmentally friendly materials that can be decomposed at 200-300° C. and will not introduce other impurities during the production process.

[0050] Preferably, the heating temperature in step S4 is 20-300°C.

[0051] If the reaction temperature is too low, the reaction speed will be too slow or even no reaction. If the reaction temperature is too high, the reaction speed will be accelerated, which will easily lead to the agglomeration of nano-metal particles. Metal elements are easily oxidized by air at high temperatures to form oxides. At the same time, solvents begin to decompose above 300°C. If the reaction time is too short, the reaction will be incomplete. If the reaction time is too long, the nano-metal particles will be in contact with the air for too long, which may accelerate the oxidation of the nano-metal particles.

[0052] Preferably, the alcohol solvent is at least one of ethanol, ethylene glycol, diethylene glycol, diethylene glycol, dipropylene glycol, glycerol or terpineol;

[0053] The mass fraction of the graphene in the composite material is 0.02 to 10%;

[0054] The mass fraction of the silicone grease or the silicone resin in the composite material is 1-10%.

[0055] Preferably, the graphene and its derivatives are at least one of graphene oxide, graphene treated with oxygen plasma, carbon nanotubes, and carbon nanotubes treated with oxygen plasma.

[0056] Graphene and its derivatives use these raw materials. The processed graphene and carbon nanotubes have oxygen-containing functional groups, which enhance the bonding strength with metals.

[0057] Graphene can be purchased directly, or graphene or its derivatives can be purchased and then treated with oxygen plasma to obtain oxidized graphene, oxygen plasma treated graphene or oxygen plasma treated carbon nanotubes.

[0058] In a specific embodiment, non-toxic and harmless organic silicone grease or silicone resin material is used to avoid the generation of harmful substances during the processing.

[0059] Preferably, the step 2 further comprises adding a dispersant and a flux;

[0060] The dispersant is polyethylene glycol or polyvinyl alcohol, and the mass fraction of the dispersant in the composite material is 1 to 10%;

[0061] The soldering flux contains rosin, and the mass fraction of the soldering flux in the composite material is 1-10%.

[0062] The function of flux is to assist the heat conduction process during the heating and drying process, accelerate the heat conduction rate, and make the paste heated evenly.

[0063] Preferably, at least one of a thickener, a sintering aid, a film-forming agent or a thixotropic agent is added;

[0064] The thickener is polyethylene glycol or polyvinyl alcohol, the sintering aid is an alkaline earth metal oxide, the film-forming agent is at least one of hydrogenated rosin, polymerized rosin or water-white rosin, and the thixotropic agent is at least one of hydrogenated castor oil or polyamide.

[0065] By using polyethylene glycol as a thickener, the viscosity of the paste can be increased, making it easier to fill gaps and maintain good contact when applying the paste. Its rheological properties allow the paste to maintain a certain degree of adhesion when heated, preventing the paste from flowing or shifting, and ensuring close contact between the heat dissipation material and the heat dissipation device. By using magnesium oxide as a sintering aid, the sintering temperature of the material can be reduced, helping the thermal interface material to form a dense structure at a lower temperature. This property is particularly important in the manufacture of temperature-sensitive electronic devices, helping to save energy and protect components from high temperature damage.

[0066] By using magnesium oxide as a sintering aid, magnesium oxide has a relatively high thermal conductivity, which can significantly improve the overall thermal conductivity of the paste, effectively fill the microscopic gaps in the material, reduce thermal resistance, enhance thermal conductivity, and help the equipment dissipate heat faster when working.

[0067] By using hydrogenated rosin as a film-forming agent, a continuous and flexible film can be formed on the surface of the paste. This film can effectively protect the filler components and prevent the material from being delaminated or falling off during use. At the same time, it improves the uniformity of the paste's coverage on the interface and makes heat conduction more uniform.

[0068] By using hydrogenated castor oil as a thixotropic agent, the thermal interface material paste can become viscous and stable when it is static, and become easy to flow when shear force is applied during extrusion or coating. Such thixotropic properties facilitate the precise application of the paste and reduce the risk of material flow or displacement at the interface between electronic devices.

[0069] Preferably, high thermal conductivity particles are added, and the mass fraction of the metal salt and the high thermal conductivity particles in the composite material is 50-97%.

[0070] The high thermal conductivity particles include at least one of polycrystalline diamond ceramics, silicon carbide ceramics, silicon nitride ceramics and beryllium oxide ceramics.

[0071] In a specific embodiment, the high thermal conductivity particles are ceramic particles, and ceramic particles are also added in step S1.

[0072] For example, the metal salts, metal oxides, reduced metals or ceramic particles used are magnetic.

[0073] Preferably, when a magnetic metal is used, a magnetic field is applied in step S4, and the direction of the applied magnetic field is perpendicular to the heat dissipation surface.

[0074] like Figure 3 When magnetic metals such as nickel, iron, and cobalt are used, a magnetic field is applied in step S4 so that the metal is magnetized and arranged in a chain shape after being generated, thereby increasing the heat dissipation performance of the thermal interface material.

[0075] Preferably, the thickness of the liquid film in step S3 is 0.1-1 mm.

[0076] The mixed liquid forms a liquid film between the heat dissipation surface and the heat sink, and maintains a height of 0.1 to 1 mm without flowing out due to surface tension.

[0077] Preferably, the dispersion treatment in step S1 is mechanical stirring, ultrasonic dispersion or homogeneous dispersion, and the dispersion treatment in step S2 is ultrasonic dispersion or homogeneous dispersion.

[0078] In step S2, ultrasonic dispersion or homogeneous dispersion is used to ensure uniform dispersion of the material.

[0079] Example 1

[0080] S1. 0.1 g of graphene, 1 g of copper acetate, and 3.52 g of anti-hemolytic acid were added to 100 ml of ethylene glycol, and a mixed solution A was obtained after mechanical stirring and ultrasonic dispersion;

[0081] S2. Add 0.05 g of polyethylene glycol and 0.1 g of rosin to solution A, add 1.5 g of silicone grease, stir mechanically, and disperse ultrasonically to obtain slurry B;

[0082] S3. Apply slurry B to the heat dissipation surface of the chip and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.85 mm between the heat dissipation surface and the heat sink.

[0083] S4. Heat to 75℃ to trigger the reaction and dry.

[0084] Example 2

[0085] S1. 0.2 g of graphene, 2 g of copper acetate, and 7.04 g of anti-hemolytic acid were added to 200 ml of ethylene glycol, and a mixed solution A was obtained after mechanical stirring and ultrasonic dispersion;

[0086] S2. Add 0.1 g of polyethylene glycol and 0.2 g of rosin to solution A, add 3 g of silicone grease, stir mechanically, and disperse ultrasonically to obtain slurry B;

[0087] S3. Apply slurry B to the heat dissipation surface of the chip and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.85 mm between the heat dissipation surface and the heat sink.

[0088] S4. Heat to 75℃ to trigger the reaction and dry.

[0089] Example 3

[0090] S1. 0.05 g of graphene, 0.5 g of copper acetate, and 1.76 g of anti-hemolytic acid were added to 50 ml of ethylene glycol, and a mixed solution A was obtained after mechanical stirring and ultrasonic dispersion;

[0091] S2. Add 0.025 g of polyethylene glycol and 0.05 g of rosin to solution A, add 0.75 g of silicone grease, stir mechanically, and disperse ultrasonically to obtain slurry B;

[0092] S3. Apply slurry B to the heat dissipation surface of the chip and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.85 mm between the heat dissipation surface and the heat sink.

[0093] S4. Heat to 75℃ to trigger the reaction and dry.

[0094] Example 4

[0095] S1. 0.1 g of graphene, 0.05 g of silicon nitride ceramic particles, 1 g of copper acetate, and 3.52 g of anti-hemolytic acid were added to 100 ml of ethylene glycol, and a mixed solution A was obtained after mechanical stirring and ultrasonic dispersion;

[0096] S2. Add 0.05 g of polyethylene glycol and 0.1 g of rosin to solution A, add 1.5 g of silicone grease, stir mechanically, and disperse ultrasonically to obtain slurry B;

[0097] S3. Apply slurry B to the heat dissipation surface of the chip and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.85 mm between the heat dissipation surface and the heat sink.

[0098] S4. Heat to 75℃ to trigger the reaction and dry.

[0099] Example 5

[0100] S1. 0.1 g of graphene, 1 g of copper acetate, and 3.52 g of ascorbic acid were added to 5 ml of ethylene glycol, and a mixed solution A was obtained after homogeneous dispersion. The graphene was treated with oxygen plasma, or graphene oxide was used;

[0101] S2.. Add 0.1 g of polyvinyl alcohol and 0.1 g of rosin to the mixed solution A, add 2 g of silicone resin, and disperse uniformly to obtain a mixed slurry B;

[0102] S3. Apply slurry B to the heat dissipation surface of the chip, and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.7 mm between the heat dissipation surface and the heat sink.

[0103] S4. Heat to 75℃ to trigger the reaction and dry.

[0104] Example 6

[0105] S1. Graphene was treated with oxygen plasma, 0.2 g of graphene, 2 g of copper acetate, and 7.04 g of ascorbic acid were added to 10 ml of ethylene glycol, and a mixed solution A was obtained after homogeneous dispersion;

[0106] S2.. Add 0.2g of polyvinyl alcohol and 0.2g of rosin to the mixed solution A, add 4g of silicone resin, and disperse them uniformly to obtain a mixed slurry B;

[0107] S3. Apply slurry B to the heat dissipation surface of the chip, and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.7 mm between the heat dissipation surface and the heat sink.

[0108] S4. Heat to 75℃ to trigger the reaction and dry.

[0109] Example 7

[0110] S1. 0.05 g of graphene oxide, 0.5 g of copper acetate, and 1.76 g of ascorbic acid were added to 2.5 ml of ethylene glycol, and a mixed solution A was obtained after homogeneous dispersion;

[0111] S2. Add 0.05 g of polyvinyl alcohol and 0.05 g of rosin to the mixed solution A, add 1 g of silicone resin, and disperse uniformly to obtain a mixed slurry B;

[0112] S3. Apply slurry B to the heat dissipation surface of the chip, and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.7 mm between the heat dissipation surface and the heat sink.

[0113] S4. Heat to 75℃ to trigger the reaction and dry.

[0114] Example 8

[0115] S1. 0.2 g of graphene, 1.5 g of nickel sulfate, and 4.5 g of hydrazine hydrate were added to 5 ml of anhydrous ethanol solvent, and a mixed solution A was obtained after homogeneous dispersion;

[0116] S2. Add 0.2 g of polyethylene glycol and 0.25 g of rosin to the mixed solution A, add 2.34 g of silicone grease, and disperse by ultrasonic to obtain a mixed slurry B;

[0117] S3. Apply slurry B to the heat dissipation surface of the chip and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.5 mm between the heat dissipation surface and the heat sink.

[0118] S4. Apply a magnetic field perpendicular to the heat dissipation surface, heat to 80°C to trigger the reaction and dry.

[0119] Example 9

[0120] S1. Graphene was treated with oxygen plasma, 0.4 g of graphene, 3 g of nickel sulfate, and 9 g of hydrazine hydrate were added to 10 ml of anhydrous ethanol solvent, and a mixed solution A was obtained after homogeneous dispersion;

[0121] S2. Add 0.2 g of polyethylene glycol and 0.25 g of rosin to the mixed solution A, add 2.34 g of silicone grease, and disperse by ultrasonic to obtain a mixed slurry B;

[0122] S3. Apply slurry B to the heat dissipation surface of the chip and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.5 mm between the heat dissipation surface and the heat sink.

[0123] S4. Apply a magnetic field perpendicular to the heat dissipation surface, heat to 80°C to trigger the reaction and dry.

[0124] Example 10

[0125] S1. 0.1 g of graphene, 0.75 g of nickel sulfate, and 2.75 g of hydrazine hydrate were added to 2.5 ml of anhydrous ethanol solvent, and a mixed solution A was obtained after homogeneous dispersion;

[0126] S2. Add 0.2 g of polyethylene glycol and 0.25 g of rosin to the mixed solution A, add 2.34 g of silicone grease, and disperse by ultrasonic to obtain a mixed slurry B;

[0127] S3. Apply slurry B to the heat dissipation surface of the chip and then cover the heat sink. The slurry forms a liquid film with a thickness of 0.5 mm between the heat dissipation surface and the heat sink.

[0128] S4. Apply a magnetic field perpendicular to the heat dissipation surface, heat to 80°C to trigger the reaction and dry.

[0129] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0130] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for processing a self-generated metal-graphene composite thermal interface material, characterized in that: Applied to chip processing, the processing method comprises the following steps: S1. adding graphene, metal salt and reducing agent into water or alcohol solvent, and obtaining mixed solution A through dispersion treatment; S2. Add at least one of silicone grease or silicone resin to the mixed solution A, and disperse it to obtain slurry B; S3. Apply slurry B to the heat dissipation surface of the chip to be processed, cover the heat dissipation surface coated with slurry B with a heat sink, and form a liquid film of slurry B between the heat dissipation surface and the heat sink; S4. The heating triggers the reaction and is maintained until drying. During the drying process, the solvent in the liquid film evaporates, and the slurry B heats up and starts to react, causing metal to form between the heat dissipation surface and the heat sink. The distance between the heat dissipation surface and the heat sink gradually decreases until the solvent completely evaporates and the heat sink is fixed to the heat dissipation surface of the chip.

2. The method for processing a self-generated metal-graphene composite thermal interface material according to claim 1, characterized in that: The metal salt includes at least one element selected from the group consisting of Cu, Ag, Ni, Ti, Au, Al, Sn, Fe, and Co. The metal salt is an organic metal salt or a hydroxide, chloride, sulfate, or nitrate of a metal.

3. The method for processing a self-generated metal-graphene composite thermal interface material according to claim 2, characterized in that: The organic metal salt is at least one of acetic acid, acetic acid, formic acid or acetylacetone metal salts.

4. The method for processing a self-generated metal-graphene composite thermal interface material according to claim 1, characterized in that: The reducing agent is at least one of ascorbic acid, glucose or hydrazine hydrate.

5. The method for processing a self-generated metal-graphene composite thermal interface material according to claim 1, characterized in that: The heating temperature in step S4 is 20-300°C.

6. The method for processing a self-generated metal-graphene composite thermal interface material according to claim 1, characterized in that: The alcohol solvent is at least one of ethanol, ethylene glycol, diethylene glycol, diethylene glycol, dipropylene glycol, glycerol or terpineol; The graphene includes graphene and its derivatives, and the mass fraction of the graphene in the composite material is 0.02-10%; The mass fraction of the silicone grease or the silicone resin in the composite material is 1-10%.

7. The method for processing a self-generated metal-graphene composite thermal interface material according to claim 1, characterized in that: It also includes adding at least one of a thickener, a sintering aid, a film former or a thixotropic agent; The thickener is polyethylene glycol or polyvinyl alcohol, the sintering aid is an alkaline earth metal oxide, the film-forming agent is at least one of hydrogenated rosin, polymerized rosin or water-white rosin, and the thixotropic agent is at least one of hydrogenated castor oil or polyamide.

8. The method for processing a self-generated metal-graphene composite thermal interface material according to claim 1, characterized in that: The method also includes adding high thermal conductivity particles, wherein the mass fraction of the metal salt and the high thermal conductivity particles in the composite material is 50-97%.

9. The method for processing a self-generated metal-graphene composite thermal interface material according to claim 1, characterized in that: When a magnetic metal is used, the magnetic field is applied in step S4, and the direction of the applied magnetic field is perpendicular to the heat dissipation surface.

10. A method for processing a self-generated metal-graphene composite thermal interface material according to any one of claims 1 to 9, characterized in that: The dispersion treatment in step S1 is mechanical stirring, ultrasonic dispersion or homogeneous dispersion, and the dispersion treatment in step S2 is ultrasonic dispersion or homogeneous dispersion.

Citation Information

Patent Citations

  • Nano metal particle doped graphene film and preparation method thereof

    CN112429722A

  • Heat dissipation paste composition using thermal conductive material coated nano carbonaceous materials and manufacturing method thereof

    KR101789172B1